THE USE OF THINK-PAIR-SHARE IN TEACHING READING COMPREHENSION - Maulida, Faiza (ELT Forum: Journal of English Language Teaching, 2017)
This study was conducted to explore the English teachersâ attitude toward the implementation of Think-Pair-Share in teaching reading comprehension. The aim was to describe the implementation of Think-Pair-Share in teaching reading comprehension by English teachers, reveal the difficulties faced by English teachers in teaching reading comprehension using Think-Pair-Share technique, and explain how the English teachers solve their problem in teaching reading comprehension using Think-Pair-Share technique. In this study, I used qualitative method. The participants of this research were all of the English teachers in SMK N 1 Randudongkal in the academic year of 2016/2017. In this research, I used questionnaire, interview, classroom observation and document analysis as data collection methods. The result revealed that the implementation of Think-Pair-Share in teaching reading comprehension was quiet different for each teacher such as including all language skills, using game as variation, or implementing Think-Pair-Share with no variation. This study showed that there were two main problems faced by the English teachers: the lack of preparation and studentsâ limited vocabulary. In conclusion, Think-Pair-Share was an interesting and helpful technique that helped English teachers in the teaching and learning process. Besides, it helped students to be actively engaged in the classroom activity.